Algumas considerações sobre leituras estativas de verbos de movimento em Português Europeu - Cunha, Luís Filipe (2019)
A significant number of the so-called verbs of motion exhibit a consistent alternation between an eventive and a stative reading. In this view, the main goal of this paper is to investigate the linguistic factors that contribute to this aspectual behaviour regarding verbs of motion in European Portuguese. In particular, we consider the fictive motion hypothesis; the influence of tenses like the Presente do Indicativo (Simple Present) and the Imperfeito (Imperfect) that stativize the predications with which they co-occur; the status of the "figure" and, finally, the role played by the different subclasses of verbs of motion, with special reference to the distinction between inherently directed verbs and manner of motion verbs. We conclude that, like other types of verbs, the aspectual feature of dynamicity seems to play a crucial role in the alternation at hand.